UTILIZATION OF EXTREME PROGRAMMING IN VILLAGE ADMINITRATION SYSTEMS TO REALIZE VILLAGE INDEPENDENCE - Mahardika, Fajar; Syafirullah, Lutfi (STKIP PGRI Tulungagung, 2026)
In the age of digital transformation, rural communities are increasingly exploring innovative methods to improve their administrative systems, strengthen governance, and achieve self-sufficiency. This paper examines the use of Extreme Programming (XP) techniques in developing and implementing Village Administration Systems (VAS) to promote village independence. XP, which focuses on iterative development, continuous feedback, and collaborative design, provides a flexible approach to tackle the unique challenges faced by village administrations, such as limited resources, diverse user needs, and varying digital literacy levels. By applying XP principles—such as continuous integration, collective ownership of code, and customer collaboration—this method enables the creation of adaptive, user-focused systems that can evolve according to community needs. Through real-time stakeholder feedback, the system can be refined to improve local governance, increase transparency, and ensure efficient resource management. The paper also explores how XP practices, including pair programming and frequent releases, help develop scalable and reliable solutions for rural areas. By fostering collaboration among local leaders, developers, and citizens, the system can empower village administrations to independently manage resources, reduce reliance on external support, and strengthen local capabilities. Ultimately, this paper aims to show how applying Extreme Programming to Village Administration Systems can enhance ownership, self-reliance, and contribute to sustainable rural development and village independence